PERAN SOSIAL DAN EKONOMI PEREMPUAN PEDAGANG SAYUR (Studi pada Perempuan Pedagang Sayur di Pasar Waydadi, Kecamatan Sukarame, Kota Bandar Lampung) - Damar Wibisono (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2014)
This study aimed to obtain a descriptive overview of the social and economic role of women vegetable vendors. The female role is focused on three aspects: (1) the social and economic role of women vegetable vendors, (2) the constraints faced by women in playing a role, and (3) the strategy of women vegetable vendors play a role in social and economic. The research was conducted in the Way Dadi market, sub Sukarame, the city of Bandar Lampung through in-depth interviews to 8 informants. The method used in this study is a qualitative method, while to obtain data and information is done by means of participant observation, in-depth interviews, and documentation. From this study it was found that the social and economic role of women vegetable vendors associated with domestic role and the role of the public. In the domestic activities of social and economic role of women vegetable vendors were as manager / manager of household finances, while the public activities of women's role as a trader are the secondary earner in the household and as one of the social network nodes. While the social and economic role played in the household, women vegetable vendors are often hit by several constraints, these constraints include: lack of access and control of women to economic resources, disability income planning, and difficulty utilizing social networks. While the strategy undertaken women vegetable vendors in overcoming these obstacles is to: control the level of household expenditure to save money, take advantage of income for saving and investment, and utilizing social networks. The strategy is a form of social and economic role of women vegetable vendors.